2018
DOI: 10.3389/fphys.2018.00331
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Patient-Specific Magnetic Drug Targeting Within the Intracranial Vasculature

Abstract: Drug targeting promises to substantially enhance future therapies, for example through the focussing of chemotherapeutic drugs at the site of a tumor, thus reducing the exposure of healthy tissue to unwanted damage. Promising work on the steering of medication in the human body employs magnetic fields acting on nanoparticles made of paramagnetic materials. We develop a computational tool to aid in the optimization of the physical parameters of these particles and the magnetic configuration, estimating the frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Through MRI and CT scans, patient specific models may be used, with clinical applications such as predicting aneurysm rupture or treatment. We use a 3D lattice-Boltzmann solver, HemeLB [27], to simulate the continuum dynamics of bloodflow through large and highly sparse vascular systems efficiently [28]. A recent validation study focused on HemeLB simulations of a real patient Middle Cerebral Artery (MCA), using transcranial Doppler measurements of the blood velocity profile for comparison, as well as exploring the effects of a change in rheology model or inlet flow rate on the results [29].…”
Section: Variety Of Other Applicationsmentioning
confidence: 99%
“…Through MRI and CT scans, patient specific models may be used, with clinical applications such as predicting aneurysm rupture or treatment. We use a 3D lattice-Boltzmann solver, HemeLB [27], to simulate the continuum dynamics of bloodflow through large and highly sparse vascular systems efficiently [28]. A recent validation study focused on HemeLB simulations of a real patient Middle Cerebral Artery (MCA), using transcranial Doppler measurements of the blood velocity profile for comparison, as well as exploring the effects of a change in rheology model or inlet flow rate on the results [29].…”
Section: Variety Of Other Applicationsmentioning
confidence: 99%
“…For researchers looking to simulate blood flow in realistic vascular geometries, the lattice Boltzmann method (LBM) is an attractive approach because it easily handles complex geometries and efficiently scales across many processors . These advantages have led to biomedical applications of the LBM such as modeling clot formation and deposition, hemodynamic patterns in stented cerebral aneurysms, and patient‐specific drug targeting . For example, HemeLB, a large‐scale LBM solver, has been extensively applied to study vascular modeling and angiogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…The computational approach must not only model the native flows in the ICA, but also the perturbations introduced by insertion of flow-diverting stents, as well as the effect on the pattern of clotting within coil-filled aneurysms. Most usefully, simulation input data should be specific to the patient in question, thus taking into account the variability of vascular geometries, vessel wall mechanics and flow-phase specific pulsatile changes in pressures and shear stresses across patients [7], or differences in physiological states for a given patient (such as heart rate or blood pressure) [8].…”
mentioning
confidence: 99%
“…Previous studies showed a comparable accuracy between LB and FEM [9], [10]. In this study, we used HemeLB, a massively parallel LB solver optimized for sparse and complex systems on large supercomputing resources [8], [11], [12]. It has been designed with the ultimate intention of allowing doctors to investigate cerebral blood flow behaviour in the human body and demonstrated its potential in hospital environment [13], [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation